2022
DOI: 10.1097/brs.0000000000004407
|View full text |Cite
|
Sign up to set email alerts
|

The Additional Economic Burden of Frailty in Adult Cervical Deformity Patients Undergoing Surgical Intervention

Abstract: Summary of Background Data. The influence of frailty on economic burden following corrective surgery for the adult cervical deformity (CD) is understudied and may provide valuable insights for preoperative planning. Objective. To assess the influence of baseline frailty status on the economic burden of CD surgery Study Design. Retrospective cohort. Materials and Methods. CD patients with frailty scores and baseline and two-year Neck Disability Index data were included. Frailty score was categorized patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…They will be used in a separate study to develop evidence-based recommendations for economic evaluations in spine surgery. Finally, a total of 130 clinical cost-effectiveness studies were included 24–153…”
Section: Resultsmentioning
confidence: 99%
“…They will be used in a separate study to develop evidence-based recommendations for economic evaluations in spine surgery. Finally, a total of 130 clinical cost-effectiveness studies were included 24–153…”
Section: Resultsmentioning
confidence: 99%
“…However, the benefits of deformity correction should always be weighed against the risks associated with such procedures. The cervical deformity population has been shown to have greater frailty, with higher numbers of comorbidities, increasing susceptibility to perioperative medical adverse events 1,28,29. In addition, complications like DJF, mechanical failure, and subsequent reoperation adversely impact the benefit of deformity correction 28.…”
Section: Discussionmentioning
confidence: 99%
“…1,28,29 In addition, complications like DJF, mechanical failure, and subsequent reoperation adversely impact the benefit of deformity correction. 28 There are relatively few studies that merge the prospect of clinical success with the development of complications in a composite measure specific to a cervical deformity cohort. With similar rates and ranges of complications to previous underwent reoperation by two years), our results provide insight into multiple considerations during preoperative planning, even when encountering a frail patient.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, as shown by nearly all of the papers collated here, frailty does not necessarily impair the capacity to benefit from surgical interventions, particularly in deformity and elective lumbar settings. According to the work of the International Spine Study Group , we can infer that in properly selected and indicated frail patients, even the cost of the episode of care is not dramatically different from more physiologically robust individuals 6. As such, while a flag for nuanced preoperative discussion, more comprehensive assessment and preoperative planning, it would appear that frailty in-and-of itself should not serve as a viable reason to decide against surgical intervention in a patient who is otherwise anticipated to benefit from such a procedure.…”
mentioning
confidence: 99%
“…In the first work, the International Spine Study Group presents results from a multicenter cohort of patients undergoing surgery for adult cervical spine deformity. 6 In this investigation, patient frailty was characterized at baseline using the modified cervical deformity frailty index originally described by Passias et al 7 With the goal of developing an econometric assessment, the International Spine Study Group then calculated utilities from two-year Neck Disability Index Scores and generated cost determinations using an elegant approach that leveraged Medicare data available through the Pearldiver platform. Overall costs were similar, irrespective of baseline frailty, as was the utility gained by two years.…”
mentioning
confidence: 99%